Reliability and validity of the Thai version of the Calgary Depression Scale for Schizophrenia - Suttajit S (Dove Medical Press, 2013)
Sirijit Suttajit,1 Manit Srisurapanont,1 Sutrak Pilakanta,1 Chawanun Charnsil,1 Siritree Suttajit21Department of Psychiatry, Faculty of Medicine, 2Faculty of Pharmacy, Chiang Mai University, Chiang Mai, ThailandAim: The purpose of this study was to assess the reliability and validity of the Thai version of the Calgary Depression Scale for Schizophrenia (CDSS) for the evaluation of depression in patients with schizophrenia.Methods: Sixty patients with schizophrenia according to Diagnostic and Statistical Manual of Mental Disorders: Fourth Edition; Text Revision (DSM-IV-TR) criteria were recruited to the study. The Thai version of the CDSS, the Montgomery–Åsberg Depression Rating Scale (MADRS), the Hamilton Depression Rating Scale, 17-item version (HDRS-17), and the Positive and Negative Syndrome Scale (PANSS) were administered. A major depressive episode diagnosed by a psychiatrist according to the DSM-IV-TR was used as a gold standard.Results: The internal consistency of the Thai version of the CDSS was very good (Cronbach's alpha = 0.869). The inter-rater reliability was found to be in substantial agreement with the intra-class correlation coefficient of 0.979. The test-retest reliability over a period of 3 days was high, with an intra-class correlation coefficient of 0.861. The Thai version of the CDSS showed significant correlations with the MADRS (r = 0.887), the HDRS-17 (r = 0.865), and the depression item of the Positive and Negative Syndrome Scale (PANSS-G6) (r = 0.833). The areas under the receiver operating characteristic curve of the CDSS, MADRS, HDRS-17, and PANSS-G6 against the DSM-IV-TR criteria for major depressive episode were 0.993, 0.954, 0.966, and 0.933, respectively. The optimal cut-off score to discriminate between depressed and non-depressed patients was 6/7, with a sensitivity of 92.31% and specificity of 97.87%.Conclusion: The Thai version of the CDSS is a reliable and valid measure for the evaluation of depression in Thai patients with schizophrenia.Keywords: CDSS, Montgomery–Åsberg Depression Rating Scale, Positive and Negative Syndrome Scale, the Hamilton Depression Rating Scale, 17-item version